Effects of local administration of tiludronic acid on experimental periodontitis in diabetic rats - Nunes, Nara L. T.; Messora, Michel R.; Oliveira, Luiz Fernando; Lisboa, Mario; Barcellos Garcia, Marina Costa; Rego, R. O. [UNESP]; Novaes, Arthur Belem; Scombatti de Souza, Sergio Luis; Ervolino, Edilson [UNESP]; Furlaneto, Flavia A. C. (Amer Acad Periodontology, 2018)
Background: Tiludronic acid (TIL) presents antiresorptive and anti-inflammatory properties and has not been evaluated in the periodontitis-diabetes mellitus (DM) association to date, to the best knowledge of the authors. This study evaluates effects of local administration of TIL on experimental periodontitis (EP) in rats with streptozotocin-induced DM. Methods: Thirty-two animals (Rattus norvegicus albinus, Wistar) were divided into groups DM/C (Control), DM/EP, DM/EP/TIL1, and DM/EP/TIL3. In EP groups, a ligature was placed around mandibular first molars. In groups DM/EP/TIL1 and DM/EP/TIL3, TIL solutions (1 and 3 mg/kg, respectively) were injected into the gingival tissue of mandibular molars every other day for 10 days, until euthanasia. Periodontal tissues were analyzed by microcomputed tomography (micro-CT), histomorphometry, immunohistochemistry (tartrate-resistant acid phosphatase [TRAP], receptor activator of nuclear factor-kappa B ligand [RANKL], osteoprotegerin, cleaved caspase 3), and quantitative reverse transcription-polymerase chain reaction (interleukin [IL]-1 beta,vascular endothelial growth factor [VEGF]). Results: In micro-CT analyses, groups DM/EP/TIL1 and DM/EP/TIL3 presented reduced alveolar bone resorption (P < 0.05). Group DM/EP/TIL3 presented decreased attachment loss (P < 0.05). The amount of TRAP-positive multinucleated cells was decreased in TIL groups (P < 0.05). Group DM/EP/TIL3 presented a lower immunolabeling pattern for RANKL (P < 0.05). TIL treatment decreased genic expression of IL-1 beta, and in group DM/EP/TIL3, expression of VEGF was increased (P < 0.05). Conclusion: Local administration of TIL promoted a protective effect against tissue destruction in EP in diabetic rats, and the dosage of 3 mg/kg of TIL promoted the best results regarding its antiresorptive and anti-inflammatory effects.
Keywords: Bone resorption; diabetes mellitus; diphosphonates; periodontitis